A pilot investigation of the Fo pattern in American English - Dyhr, Niels (Annual Report of the Institute of Phonetics University of Copenhagen, 1980)
Fourteen declarative sentences were recorded by one native speaker of American English. The Fo pattern (the Fo movement within the stress group) was investigated, and a model was proposed. This model was compared to one based on identical material, but with a British speaker.